Design of wearable and wireless multi-parameter monitoring system for evaluating cardiopulmonary function. (September 2017) - Li, Shih-Hong; Lin, Bor-Shing; Wang, Chen-An; Yang, Cheng-Ta; Lin, Bor-Shyh
Highlights: A wearable and wireless multi-parameter monitoring system under 6MWT. Monitoring real-time SpO2, heart rate, walking information simultaneously under 6MWT. Measuring SpO2, HR, and indoor walking distance, similar to the conventional device. The cardiopulmonary function of groups of sportsmen is good than normal healthy ones. A good multi-parameter monitoring system for evaluating cardiopulmonary function. Abstract: The 6-minute walking test (6MWT) is the test most commonly used to evaluate cardiopulmonary function in patients with respiratory or heart disease. However, there was previously no integrated monitoring system available to simultaneously record both the real-time cardiopulmonary physiological parameters and the walking information (i.e., walking distance, speed, and acceleration) during the 6MWT. In this study, then, a wearable and wireless multi-parameter monitoring system was proposed to simultaneously monitor oxygen saturation (SpO2 ), heart rhythm, and the walking information during the 6MWT. A multi-parameter detection algorithm was also designed to estimate the heart rate effectively. The results of the study indicate that this system was able to reveal the dynamic changes and differences in walking speed and acceleration during the 6MWT. As such, the system has the potential to provide a more integrated approach to monitoring cardiopulmonary parameters and walking information simultaneously during the 6MWT. The proposed system warrants further investigation as an assistive assessment tool in evaluating cardiopulmonary function and may be widely applied in cardiopulmonary-related and sports medicine applications in the future.